Poetics of the Body in Artistic Creation in Marina Abramović and Elke Hering - Gottardi, Pedro; Peruzzo, Leomar; Carvalho (Universidade Regional de Blumenau – FURB, Blumenau/SC, Brazil), Carla (Revista Brasileira de Estudos da Presença, 2022)
This study contemplates the body as a reflective place to observe artistic creations, having two artists as inspiring perspective: Marina Abramović and Elke Hering. The general goal was to investigate the dialogues established by the artists’ works and the body as aesthetic potency. The analytical observation of Abramović’s performance and Hering’s work allowed a dive into the space of the body as a field of sensitive potentialities and possible relations with knowledge in art. In the end, congruences, similarities, the distances of the bodies created in art as thematic and support make discussions in the field of aesthetic experience in art possible.